2021
DOI: 10.2478/nispa-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Concept of Providing Local Public Services Based on ICT

Abstract: The public sector faces the challenge of re-evaluating public service delivery mechanisms with a citizen orientation. The eGovernment concept should not only focus on delivering a large number of services to increase efficiency and effectiveness when deciding on a top-down approach, based on government needs, but decisions should be made on the basis of citizens’ needs, a bottom-up approach. The object of the paper is to identify problems of public service innovations demand and supply, which determinate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…25 Tahun 2009 Tentang Pelayanan Publik, pengaturan ini dimaksud untuk memberikan kepastian hokum dalam hubungan antara masyarakat dan penyelenggara dalam pelayanan publik. Selain itu, pengaturan mengenai pelayanan public bertujuan agar terwujudnya batasan dan hubungan yang jelas tentang hak, tanggungjawab, kewajiban, dan kewenangan seluruh pihak yang terkait dengan penyelenggaraan pelayanan publik; agar terwujudnya system penyelenggaraan pelayanan publik yang layak sesua idengan asas-asas umum pemerintahan dan korporasi yang baik; agar terpenuhinya penyelenggaraan pelayanan public sesuai dengan peraturan perundang-undangan; dan agar terwujudnya perlindungan dan kepastian hokum bagi masyarakat dalam penyelengaaran pelayanan publik (Enang et al, 2022;Meričková & Muthová, 2021;Ojasalo & Kauppinen, 2022;Osborne & Strokosch, 2022;Trischler et al, 2019).…”
Section: Pelayanan Publikunclassified
“…25 Tahun 2009 Tentang Pelayanan Publik, pengaturan ini dimaksud untuk memberikan kepastian hokum dalam hubungan antara masyarakat dan penyelenggara dalam pelayanan publik. Selain itu, pengaturan mengenai pelayanan public bertujuan agar terwujudnya batasan dan hubungan yang jelas tentang hak, tanggungjawab, kewajiban, dan kewenangan seluruh pihak yang terkait dengan penyelenggaraan pelayanan publik; agar terwujudnya system penyelenggaraan pelayanan publik yang layak sesua idengan asas-asas umum pemerintahan dan korporasi yang baik; agar terpenuhinya penyelenggaraan pelayanan public sesuai dengan peraturan perundang-undangan; dan agar terwujudnya perlindungan dan kepastian hokum bagi masyarakat dalam penyelengaaran pelayanan publik (Enang et al, 2022;Meričková & Muthová, 2021;Ojasalo & Kauppinen, 2022;Osborne & Strokosch, 2022;Trischler et al, 2019).…”
Section: Pelayanan Publikunclassified
“…Chen et al (2020) systematically reviewed the literature on PSIs and recommended future studies to evaluate the ways and conditions of PSI to deliver continuity to public values. PSI are more likely to sustain when they are user-oriented and bottom-up (Meričková & Muthová, 2021). However, research also found that the lack of user-friendliness and approaches have led to citizens' dissatisfaction (Meričková & Muthová, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…PSI are more likely to sustain when they are user-oriented and bottom-up (Meričková & Muthová, 2021). However, research also found that the lack of user-friendliness and approaches have led to citizens' dissatisfaction (Meričková & Muthová, 2021). Thus, the engagement of front-liners or municipality employees in PSIs is important because they interact more intensely with users (Meričková & Muthová, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation